2022
DOI: 10.3390/buildings12020241
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Modifying Methods on Physical, Mechanical and Thermal Performance of Cellular Geopolymers as Thermal Insulation Materials for Building Structures

Abstract: Geopolymers represent a new class of inorganic materials that have great potential for practical application due to the properties of used raw materials, as well as the peculiarities of the cementitious matrix structure formed during the geopolymerization process. Cellular geopolymer specimens were produced in this study using class F fly ash product, which is characterized by low reactivity during geopolymerization. Several standard methods, as well as microstructural studies were applied to evaluate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The binder obtained by sintering citrogypsum is a white powder with a specific surface area (SSA) of the order of 350-400 m 2 /kg [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binder obtained by sintering citrogypsum is a white powder with a specific surface area (SSA) of the order of 350-400 m 2 /kg [4].…”
Section: Methodsmentioning
confidence: 99%
“…1). At present time, the technology has been developed for processing this waste into a binder by sintering it in drum dryers [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the reference [30], the authors investigated the modification of metakaolin-based geopolymer with silicon phosphate to provide waterproof characteristics. Reference [31] is devoted to the combination of fly ash and various mineral additives (Portland cement, metakaolin, kaolin, citrogypsum) and the study of their effect on mechanical, thermal and physical characteristics of geopolymer cement. The literature review showed that scientific research focused on the study of geopolymers based on natural aluminosilicates is widespread.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, geopolymer mortars produced with low CaO binders have higher fire resistance characteristics compared to their cementitious or high CaO counterparts. In addition, the compressive strength of a cellular geopolymer produced with class F fly ash and a foam agent used as a thermal insulation material was increased up to 250% after a thermal exposure of 600 • C [62]. In another study on the microstructure change of fly ash-based geopolymer material under high temperatures, it was noted that the alkaline-activated matrix became denser and the strength increased owing to the high solubility of aluminosilicate components that result in the synthesizing of vitreous phases and the formation of new nanosized crystals [63].…”
Section: Introductionmentioning
confidence: 99%